2007
DOI: 10.1007/s11547-007-0206-9
|View full text |Cite
|
Sign up to set email alerts
|

Malpractice stress syndrome in radiologists and radiotherapists: perceived causes and consequences

Abstract: Radiologists are well acquainted with medical malpractice and its causes; however, they have limited familiarity with clinical risk management practices and often ignore procedures of informed consent. A targeted educational effort is required to overcome these shortcomings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 17 publications
2
24
0
7
Order By: Relevance
“…4 The study conducted in Italy showed that the relationship between age and the probability of being sued is contradictory because most of their respondents thought that older radiologists were more proficient than younger ones, though the youthful may be more up to date with advanced technology. 8 By contrast, their respondents believed that newer radiologists are inclined to make more mistakes than are their more experienced coworkers. 8 Meanwhile, it was theorized in the same study that advanced age and deteriorating cognitive skills might affect the capacity to identify radiologic findings.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…4 The study conducted in Italy showed that the relationship between age and the probability of being sued is contradictory because most of their respondents thought that older radiologists were more proficient than younger ones, though the youthful may be more up to date with advanced technology. 8 By contrast, their respondents believed that newer radiologists are inclined to make more mistakes than are their more experienced coworkers. 8 Meanwhile, it was theorized in the same study that advanced age and deteriorating cognitive skills might affect the capacity to identify radiologic findings.…”
Section: Discussionmentioning
confidence: 94%
“…8 By contrast, their respondents believed that newer radiologists are inclined to make more mistakes than are their more experienced coworkers. 8 Meanwhile, it was theorized in the same study that advanced age and deteriorating cognitive skills might affect the capacity to identify radiologic findings. 8 Certainly as years in practice extend, the prospect of being sued at least once increases with increasing age as more cases are read.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations